Meningkatkan Hasil Belajar IPA Siswa Kelas VIII-A MTS Alhamid Banjarmasin Melalui Model Pembelajaran Kooperatif Tipe TAI - Widha Nur Hasnah; M. Arifuddin Jamal; Sri Hartini (Berkala Ilmiah Pendidikan Fisika, 2015)
The low of student learning outcomes because students are less active during learning, that’s why the need conduct research that aims to improve student learning outcomes. This study describes (1) lesson plan, (2) learning outcomes, (3) social skills. This research is classroom action research hopkins model that includes planning, implementation, observation and reflection as much as 3 cycles. Data collection techniques such as observation, testing, and documents. Data analysis of quantitative and qualitative descriptive. The results showed that (1) the percentage of first cycle lesson plan (RPP) implementation is 80,00%, 91,33% in second cycle and third cycle is 97,33%, (2) mastery learning outcomes of students has increased from first cycle 51,61% , 77,43% in the second cycle, and to 87.04% in the third cycle, (3) the student's social skills in the first cycle of 96,97% with very good category, II 97,86% with very good category, and 97,86% in the third cycle with very good category, Retrieved conclusion that cooperative learning  model TAI type can improve student learning outcomes with focusing in drill to students can increase creavity and students social skill with give a motivation and guidance to student which has a problem on study class.